A scoping review on active vs. passive range of motion approaches to treat heterotopic ossification at the elbow - Siegel, Patricia; Smith, Shanna; Stark, Emily; Burns, Cole; Dionne, Timothy P. (Frontiers in Rehabilitation Sciences, 2024)
Objective The objective of this scoping review is to synthesize and clarify literature on the effectiveness of active and passive range of motion therapy techniques to address range of motion in people with heterotopic ossification (HO), and to provide guidance to therapists in clinical decision-making based on current evidence. Method To find articles that included therapeutic interventions to maintain or improve range of motion in people with heterotopic ossification, the authors searched the following databases: Cochrane Database of Systematic Reviews, PubMed, CINAHL, PsychINFO, Web of Science, and OTSeeker. To ensure that the search was comprehensive, the authors also searched Burns and Trauma, Burns Journal, Burns Open, and the Journal of Hand Therapy. Searches were limited to peer-reviewed articles published in the English language. No publication date limits were set. The Physiotherapy Evidence Database PEDro scale was utilized to measure the validity of the methodological quality of each article. Results Five studies met the inclusion criteria.. Two studies emphasized that passive range of motion was effective in less than 50% of their subjects, while the other three studies utilized active range of motion only, reporting 50% of patients did not require surgery. Discussion/conclusion There is insufficient evidence to determine effective therapeutic management of HO and the literature that does exist is contradictory and inconclusive. Future research is necessary to determine if any effectiveness of manual therapeutic approaches exists for patients with HO.